IMPACTS OF GLYPHOSATE ON PLANT GROWTH PROMOTING ABILITIES OF RHIZOBACTERA ISOLATED FROM AGRICULTURAL SOIL - EZAKA, E.; OYEDELE, A.O.; UTHMAN , A.C.O.; ADEDIRAN, A. B. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
The contamination of agricultural farm lands due to pollution arising from excessive and indiscriminate use of herbicide, such as glyphosate, leads to the reduction in densities of important soil microbial communities, which play several roles such as nutrient cycling and other key roles necessary for the maintenance of soil fertility. Due to the adverse effects of this chemical to non-target beneficial organism, this study was designed to evaluate the effect of different concentrations of glyphosate (3.1, 7.2 and 14.4 mg/ml) on plant growth promoting (PGP) ability of Bacillus mojavensis, Pseudomonas aeruginosa, Alcaligenes faecalis, Pseudomonas syringae and Bacillus cereus. The effects of different concentrations of glyphosate on Indole acetic acid (IAA) production, potassium and phosphorus solubilisation and nitrogen fixing abilities of the isolates were evaluated using Salkowsky, Atomic Absorption Spectroscopy (AAS), vanadomolybdate and microkjedhal method. The highest amount of IAA was recorded by Pseudomonas aeruginosa and least by Bacillus mojavensis. The results of P-solubilisation followed the same trends with Pseudomonas aeruginosa having the highest amount of P-solulisation while the least was recorded by Bacillus mojavensis. The results of K-solubilisation were significantly different (P?0.05) at different concentrations of glyphosate. The nitrogen fixing ability of the isolates were also affected by the increase in concentration of glyphosate. All the isolates showed the least nitrogen fixed at the concentration of 14.4mg/ml. The result of this study has revealed the need for the farmer to stick to recommended or even below the recommended rate of glyphosate application to reduce its deleterious effects on the beneficial soil organism and to enhance sustainable soil quality.